REGRESSION OF RETINAL MICROVASCULAR ALTERATIONS IN PATIENTS WITH RHEUMATOID ARTHRITIS TREATED WITH ABATACEPT, AN INHIBITOR OF LYMPHOCYTIC CO-STIMULATION. (June 2018) - Caletti, S.; Piantoni, S.; De Ciuceis, C.; Coschignano, M.A.; Rossini, C.; Airò, P.; Tincani, A.; Rosei, C. Agabiti; Kumar, R.; Rizzoni, D.
Abstract : Objective: It has been previously demonstrated that T lymphocytes may be involved in the development of hypertension and microvascular remodeling, and that circulating T effector lymphocytes may be increased in hypertension (De Ciuceis C et al, Am J Hypertens 2017, 30:51–60; Itani HA et al. Hypertension 2016; 68:123–132). In particular, Th1 and Th 17 lymphocytes may contribute to the progression of hypertension and microvascular damage. Abatacept is a fusion protein composed of the Fc region of the immunoglobulin IgG1 fused to the extracellular domain of CTLA-4 that binds to the CD80 and CD86 molecule, and prevents activation of T cells, avoiding CD28 repetitive engagement. Abatacept is presently indicated for treatment of moderate to severe active rheumatoid arthritis in adults (aged 18 years or over) who have not had an adequate response to other drugs. The aim of our study was to non-invasively investigated morphological characteristics of retinal arterioles in patients with rheumatoid arthritis before and after treatment with abatacept. Design and method: In the present study we enrolled 5 patients with rheumatoid arthritis. The wall to lumen ratio (WLR) of retinal arterioles was measured by adaptive optics (RTX-1, Imagine Eyes, Orsay, France), a recently validated technique (De Ciuceis C, in press in J Hypertens) for non-invasive assessment of retinal arteriolar morphology, providing also an estimation of internal and external diameters and wall cross-sectional area. Morphological evaluations were performed at baseline, after 6 months and after 12 months of treatment Results: The results obtained are reported in the Table (* < 0.05, **p < 0.01 vs. baseline). Figure. No caption available. Conclusions: Our data suggest that a reduction in WLR, wall thickness and wall cross-sectional area was observed after treatment for 12 months with abatacept, thus suggesting the possibility to induce a regression of microvascular abnormalities through a modulation of the immune system.